The preparedness assessment of highly qualified female air-pistol shooters. - Roshchin I.G (Kharkov National Pedagogical University, 2011)
It is defined the level of skill of the members of women's national team of Ukraine on firing air pistol. It is analyzed the results of these athletes performances at the Ukrainian and international competitions in the period 2005-2010, that allowed the development of their rating. It is established that the individual variation points athletes does not depend on the level of sport performance (V = 0,8 ч 1,1%).